Education and Research in New Materials: Looking at the market, working with manufacturers - Silvia G. Fernandez-Villa; Margarita San Andrés; Ruth Chércoles; Isabel M. García (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Research is a core element for the development and improvement of education, especially in the field of Conservation and Restoration of Heritage. This article shows a particular example of the linkages, benefits and synergies between research and teaching in the context of the study and analytical characterisation of the new polymeric materials used in conservation.